2020
DOI: 10.3389/fpsyg.2020.588580
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Trends During the COVID-19 Crisis: How Awe, Coping, and Social Norms Drive Utilitarian Purchases

Abstract: As the coronavirus disease 2019 (COVID-19) crisis continues to worsen globally, there exists a widespread enthusiasm for buying utilitarian products in the retail market, irrespective of culture or nationality. However, the questions of whether and why being involved in a public health emergency like the COVID-19 crisis could modify consumer behaviors have been underexplored by previous literature. Drawing on the theory of awe that highlights the important role in influencing human behaviors when they are faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 51 publications
1
43
0
1
Order By: Relevance
“…Another contributing aspect is the connection between social norm and perceived scarcity. Previous literature have identified social norms as behaviours adopted during the COVID-19 crisis and focused on social norm compliance such as purchasing of masks or hand sanitisers ( Yang et al, 2020 ). This study instead suggests that under the Emergent Norm theory, a modification of a social norm can alter one's perception of scarcity.…”
Section: Implicationmentioning
confidence: 99%
“…Another contributing aspect is the connection between social norm and perceived scarcity. Previous literature have identified social norms as behaviours adopted during the COVID-19 crisis and focused on social norm compliance such as purchasing of masks or hand sanitisers ( Yang et al, 2020 ). This study instead suggests that under the Emergent Norm theory, a modification of a social norm can alter one's perception of scarcity.…”
Section: Implicationmentioning
confidence: 99%
“…In addition, people are more likely to follow others' attitudes and behaviours when exposed to risk events such as SARS [72,73]. Notably, the recent study from Yang et al [74] found that the pandemic has led people to be more willing to obey social norms, and follow collective behaviours in the consumption trends during the COVID-19 crisis. Therefore, the IOC should be positively associated with consumers' subjective norms.…”
Section: The Impact Of Covid-19mentioning
confidence: 99%
“…Multiple studies also emphasize the idiosyncratic nature of uncertainty shocks (pandemics, natural disasters, mass shootings, etc.) and ways in which they affect stability-seeking consumption behaviour (Minton & Cabano, 2021;Yang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%